Pengaruh Elisitor Biosaka Dan Pupuk Npk Terhadap Serapan Hara Dan Hasil Kacang Hijau - Maria Klara Salli; Masria Masria (Jurnal Penelitian Pertanian Terapan, 2025)
The productivity of mung beans in East Nusa Tenggara for the last five years has been recorded at around 0.89 tons/ha, which is lower than the potential yield of superior varieties. This research focuses on increasing the productivity of mung beans through fertilization and the use of renewable technologies, especially bodacious elicitors, and NPK fertilizers. The study aimed to examine the effect of bodacious elicitation and NPK fertilizers on yield components and nutrient uptake from local varieties of mung bean. Using a Random Design of a group of factorial patterns, the first factor has two levels: without biosaka (B0) and with biosaka (B1).The second factor is the dose of NPK Phonska Plus fertilizer, consisting of 4 levels, namely 100% NPK (P1 = 250 kg/ha), 80% NPK (P2 = 200 kg/ha), 60% NPK (P3 = 150 kg/ha) and 40% NPK Plus (100 kg/ha).  The data was analyzed using variance analysis and continued with Duncan's Multiple Range Test. The results showed that the treatment could increase the nitrogen (N), phosphorus (P), potassium (K), and cation exchange capacity (KTK) of soil, as well as nutrient uptake at lower NPK doses. In addition, it positively affected the number of pods, pod weight, 100 seeds, and mung bean seed yield. The combination of biosaka with a dose of 40% NPK resulted in higher mung bean seeds.. This study recommends using biosaka as one of the strategies to increase mung bean productivity with more efficient NPK fertilization to support agricultural sustainability in East Nusa Tenggara.